Hakikat dan Sejarah Perkembangan Bahasa Indonesia - Ira Yuniati; Tuhfah Muslihah; Asriana Nur Ameliah; Dea Rahayu; Nivi Yulia Sapitri; Reza Meitista Putri (Journal of Innovation in Teaching and Instructional Media, 2026)
This study analyzes the nature of Indonesian as a system of symbols and collective identity, reconstructs its historical dynamics from the Old Malay era to its unification as a national language, and explores contemporary sociolinguistic challenges in the era of globalization and digitalization. A qualitative library-research approach was employed, combining historical analysis, content analysis, and source triangulation to examine language policy documents and related literature. The findings reveal that the transformation of Malay into Indonesian reflects successful egalitarian and inclusive sociolinguistic engineering, while post-independence corpus standardization (PUEBI/EYD) effectively built national integration. However, in the contemporary era, the hegemony of standard language faces challenges from linguistic hybridity driven by code-switching and informal digital language variation on social media. This study uniquely integrates three dimensions of inquiry philosophical-conceptual, historical-chronological, and digital sociolinguistic which prior studies have generally treated separately, offering a comprehensive analysis of Indonesian's evolution and contemporary challenges. The study recommends a policy reorientation from a centralistic top-down model toward an adaptive bottom-up approach responsive to modern linguistic ecology, without sacrificing Indonesian's unifying function. This research contributes a holistic framework for understanding Indonesian as an ideological project in a postcolonial state, offering actionable insights for language policymakers in navigating the tension between standardization and digital-era linguistic diversity while preserving national cohesion.